Levetiracetam in lactation: How much is excreted into human breast milk?. Issue 1 (1st July 2021) - Dinavitser, Natalie; Kohn, Elkana; Berlin, Maya; Brandriss, Nurit; Bar‐Chaim, Adina; Keidar, Rimona; Livne, Ayelet; Stepensky, David; Berkovitch, Matitiahu; Sheinberg, Revital
Abstract : Aims: In breastfeeding women, anti‐epileptic therapy can lead to infant toxicities, even with newer anti‐epileptic drugs such as levetiracetam. This study assessed levetiracetam breastmilk excretion and its correlation with the maternal oral dose and serum concentrations. Methods: Women with epilepsy treated with levetiracetam were recruited to this study and completed a questionnaire. Levetiracetam concentrations were determined in serial breastmilk samples (pre‐dose to 12 h post‐dose period) and in a single pre‐dose maternal serum sample. Results: Twenty breastfeeding women and 21 infants (one woman with twins; 16 fully and five partially breastfed infants) participated in this study. The trough breastmilk/serum ratio of levetiracetam was 0.98 ± 0.20. The infant levetiracetam daily dose was 5.39 ± 1.96 and 2.70 ± 0.98 mg . kg ‐1. d −1, and the relative infant dose (RID) was 13.8 ± 3.1% and 6.9 ± 1.6% in the fully and partially breastfed infants, respectively. Substantial correlations between the levetiracetam dose, maternal serum and breastmilk trough concentrations, and breastmilk AUC values were found. Three women reported somnolence in their fully breastfed infants, which resolved shortly after switching to partial breastfeeding. All the infants gained weight according to their age. Conclusions: Infant levetiracetam exposure via the breastmilk was close to the safety thresholds (trough breastmilk/serum ratio slightly below 1, RID > 10% in fully breastfed infants), and infant somnolescence reports could be related to exposure of the infants to levetiracetam via breastmilk. Further studies are warranted to reveal the short‐ and long‐term safety of levetiracetam in breastfeeding.